Improving Students’ Participation In Lecturing Through Cooperative Learning Model In Jigsaw Type - Hendrik Pandu Paksi (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2017)
Based on the observations by the researcher during being a lecture in S1 degree[G1] of PGSD in education UNESA, the level students’ participation at the time of lecturing is not as expected. In the previous research, the lecturing activities which have done until mid-semester, the researcher observed 31 students, only a small percentage of students actively participated in the way of asking questions, answering questions, also conveying an idea. In the previous result [G2] [G3] showed that the level of students’ participation in the course less than 35%. Whereas, the researcher expects every student should more actively to contribute either assessment of course participation which has 2 points, equal with mid-term test point (UTS). At least, the target of the researcher is 50% or more than students' participation actively. So, classroom action research is needed. In this research, the observer [G4] applied jigsaw learning model as the basic concept [G5] ofPPKn course particularly. Jigsaw learning model was chosen because the steps used were known be able involve all students as the result that in the course every students will be prosecuted as skilled team activities and work well together independently as well as group to understand the concept or material which being learning, therefore it can move the students [G6] [G7] to participate in the way of asking questions, answering questions, also conveying idea.[G8] [G9] [G10] This research used two cycles which include four steps i.e. planning, action, observation, and reflection. The result of observation and reflection in every cycle, it can conclude the first cycle was successful with the participate rate 64,5% out of 31 students who attend in lecturing. The second cycle was successful reached 73,3% out of 30 students in lecturing. In the research cycle 1 and cycle 2 were reliable. Therefore, cooperative learning model in jigsaw type can improve students’ participation in lecturing.